2018
DOI: 10.1080/08941939.2018.1458925
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hidden Blood Loss Between Three Different Surgical Approaches for Treatment of Thoracolumbar Fracture

Abstract: There was a substantial HBL in the treatment of thoracolumbar fractures, which was neglected by surgeons. Further investigation is necessary to study the risk factors for surgery on HBL in treatment of thoracolumbar fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 17 publications
4
25
1
Order By: Relevance
“…EBL in surgery for traumatic thoracolumbar fracture using a conventional open method was over 1000 mL 11 , when calculating EBL using the same formula as used in this study. In the present study, EBL in surgery using PPS was 590 mL in group E and 441 mL in group L. These results indicated that EBL in surgery using PPS was less than that using a conventional open method, which is consistent with a previous report 12 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…EBL in surgery for traumatic thoracolumbar fracture using a conventional open method was over 1000 mL 11 , when calculating EBL using the same formula as used in this study. In the present study, EBL in surgery using PPS was 590 mL in group E and 441 mL in group L. These results indicated that EBL in surgery using PPS was less than that using a conventional open method, which is consistent with a previous report 12 .…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, considering not only IBL but also EBL including HBL in surgery for traumatic thoracolumbar fracture is necessary, especially in surgery using PPS. EBL, IBL, and HBL in surgery using PPS are lower than those using a paraspinal or conventional open approach 12 . EBL in surgery for traumatic thoracolumbar fracture using a conventional open method was over 1000 mL 11 , when calculating EBL using the same formula as used in this study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Previous studies have explored the influence of age, gender, body mass index (BMI), and fracture type on HBL. [10,11] Until now, no study explored the effect of matching degree of intramedullary nail to marrow cavity on HBL. The present aimed to explore the effect of the ratios of marrow cavity diameter to intramedullary nail diameter from different layers on HBL, OBL, and total blood loss (TBL) in the perioperative period during using PFNA-II for femoral intertrochanteric fracture.…”
Section: Introductionmentioning
confidence: 99%